2009
DOI: 10.1055/s-0029-1220731
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3R577X Polymorphism and Israeli Top-level Athletes

Abstract: A common genetic variation in the alpha-actinin-3 ( ACTN3) gene causes a replacement of an arginine (R) with a premature stop codon (X) at amino-acid 577 (rs1815739). While the R allele has been found to be associated with power-oriented performance, the XX genotype may be linked with endurance ability. To test this hypothesis, we studied the distribution of ACTN3 genotypes in 155 Israeli athletes (age=35.9+12.2 years) classified by sport (endurance runners and sprinters) and in 240 sedentary individuals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
1
11

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 26 publications
14
127
1
11
Order By: Relevance
“…It has been demonstrated that the RR genotype is over-represented in several groups of power-athletes (Druzhevskaya et al 2008;Eynon et al 2009e;Niemi and Majamaa, 2005;Yang et al 2003), with the overall conclusion that this specific genotype may confer an advantage in power-oriented sports events, e.g. sprint, jumping or throwing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that the RR genotype is over-represented in several groups of power-athletes (Druzhevskaya et al 2008;Eynon et al 2009e;Niemi and Majamaa, 2005;Yang et al 2003), with the overall conclusion that this specific genotype may confer an advantage in power-oriented sports events, e.g. sprint, jumping or throwing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory indicated that the R577X substitution in the ACTN3 gene (Eynon et al 2009e) and several variants in the PPARGC1A-NRF-TFAM pathway (Eynon et al 2009a;2009b;2009c;2009d;) are associated with elite athletic status. We also suggested that in general, endurance athletes have a polygenic profile that is more adjusted for mitochondrial biogenesis, as opposed to power athletes or non-athletic controls (Eynon et al 2010).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations